A novel Narrative e-Writing Intervention for parents of children with chronic life-threatening illnesses : protocol for a pilot, open-label randomized controlled trial - Ho, Andy Hau Yan (2021)
Background: A novel evidence-based Narrative e-Writing Intervention (NeW-I) has been developed and tested in Singapore to advance psychosociospiritual support for parents of children with chronic life-threatening illnesses. NeW-I is informed by an international systematic review and a Singapore-based qualitative inquiry on the lived experience of parental bereavement and supported by literature on anticipatory grief interventions for improving the holistic well-being of parent caregivers of seriously ill children. Objective: This study's aim was to provide an accessible platform, NeW-I—which is a strengths- and meaning-focused and therapist-facilitated mobile app and web-based counseling platform—that aims to enhance quality of life, spiritual well-being, hope, and perceived social support and reduce depressive symptoms, caregiver burden, and risk of complicated grief among parents of children with chronic life-threatening illnesses. Methods: The NeW-I therapist-facilitated web-based platform comprises a mobile app and a website (both of which have the same content and functionality). NeW-I has been implemented in Singapore as a pilot open-label randomized controlled trial comprising intervention and control groups. Both primary and secondary outcomes will be self-reported by participants through questionnaires. In collaboration with leading pediatric palliative care providers in Singapore, the trial aims to enroll 36 participants in each group (N=72), so that when allowing for 30% attrition at follow-up, the sample size will be adequate to detect a small effect size of 0.2 in the primary outcome measure, with 90% power and two-sided significance level of at least .05. The potential effectiveness of NeW-I and the accessibility and feasibility of implementing and delivering the intervention will be assessed. Results: Funding support and institutional review board approval for this study have been secured. Data collection started in January 2019 and is ongoing. Conclusions: NeW-I aspires to enhance holistic pediatric palliative care services through a structured web-based counseling platform that is sensitive to the unique cultural needs of Asian family caregivers who are uncomfortable with expressing emotion even during times of loss and separation. The findings of this pilot study will inform the development of a full-scale NeW-I protocol and further research to evaluate the efficacy of NeW-I in Singapore and in other Asian communities around the world.